A Translation Analysis Of English Phrasal Verb In Endless Night Novel And Its Translation - Jamil, Burhan Elrosyid; , Dra. Dwi Haryanti, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
This research studies about the translation analysis of English phrasal verb in Endless Night novel. The objectives of the study are to classify the translation shift of phrasal verb and to describe the equivalence of phrasal verb and its translation. This research applies descriptive qualitative research. By applying this method, the objects used to be analyzed are phrasal verbs on both novels. The are in the forms of sentences and clauses containing phrasal verbs. The writer takes the data from Endless Night and its translation Malam Tanpa Akhir. In collecting the data, the writer uses documentation method and technique of coding which can be found in both of novel Endless Night novel and its translation. The research is describing the shifts of translation and equivalence translation of phrasal verb. To achieve these objectives, he compares two languages based on the level and category shift and the equivalence of translation. The theories are taken from Catford, Newmark, and Nida Eugene. The results of the research show that first, from 185 data, the writer finds 153 data or 82, 70% belong level shift that consists of phrasal verb into verb are 142 data or 76, 75%, phrasal verb into adjective are 3 data or 1, 62%, phrasal verb into adverb is 1 datum or 0, 54%, and phrasal verb into clause is 4 data or 2, 16%. Second, he finds 33 data or 17, 83% belong to structure shift consists of phrasal verb into verb phrase are 25 or 13, 51%, and untranslated phrasal verbs are in 8 data or 4, 32%. Third, from 185 data, there are equivalence and non equivalence. The researcher find 178 data or 96, 21% belong to equivalence translation that consists of formal equivalence are 102 data or 55, 13% and dynamic equivalence are in 76 data or 41, 08%. And 7 data or 3, 78% are nonequivalence.